A study on impact of online-service quality on customer satisfaction in e- retailing business - Salem Perumal, Thenmozhi; Sundaram, Vijayanand; Arunachalam, Arumugam (Serbian Journal of Management, 2021)
This paper checks the effect of service quality in the online retail business on customer satisfaction along with the association of the demographic variables through the opinion from the respondents particularly 524 college students in India selected through purposive sampling method. The goodness of model fit was found using Structural equation Modelling (SEM) of AMOS and the relationship between e-service quality and customer satisfaction was analyzed through Inter -correlation and Regression analysis. The results show that e-service quality factors have a positive impact and also highlighted as a significant predictor for customer satisfaction. The study also revealed that service recovery is acting as a mediating factor between service failure and customer satisfaction. The output of this study will support the online retailers to formulate their strategies in view to provide very good and excellent services to their customers.